Treatment of textile wastewater - Han, Meiqi. (2011)
Textile industries around the world generate a massive amount of wastewater, all year round. The purpose of this project is to determine an efficient and cost-effective method for the treatment of textile wastewater. In most textile wastewater treatments, colour reduction is the major problem, before these wastewaters can be legally discharged into the various watercourses. Hence, colour, together with COD, TSS, MLSS and the pH are all concerned parameters that would be tested after every HRT cycle.In this project, the wastewater is synthesised in accordance with textile wastewaters generated in Malaysia, Thailand and Vietnam. The synthetic wastewater was first passed through the activated sludge process, and the final effluent was analysed. The second batch of wastewater was then passed through the modified activated sludge process, with chemical coagulant Al2SO4 added into the process.